Are Remittances Good for Labor Markets in LICs, MICs and Fragile States? - Chami, Ralph; Ernst, Ekkehard; Fullenkamp, Connel; Oeking, Anne. (Washington, D.C. : International Monetary Fund, 2018)
We present cross-country evidence on the impact of remittances on labor market outcomes. Remittances appear to have a strong impact on both labor supply and labor demand in recipient countries. These effects are highly significant and greater in size than those of foreign direct investment or offcial development aid. On the supply side, remittances reduce labor force participation and increase informality of the labor market. In addition, male and female labor supply show significantly different sensitivities to remittances. On the demand side, remittances reduce overall unemployment but benefit mostly lower-wage, lowerproductivity nontradables industries at the expense of high-productivity, high-wage tradables sectors. As a consequence, even though inequality declines as a result of larger remittances, average wage and productivity growth declines, the latter more strongly than the former leading to an increase in the labor income share. In fragile states, in contrast, remittances impose a positive externality, possibly because the tradables sector tends to be underdeveloped. Our findings indicate that reforms to foster inclusive growth need to take into account the role of remittances in order to be successful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet